Sexual political violence from october to december 2019 in Chile: analysis of context and institutional practices of state agents - Pérez Cáceres, Danitza; Troncoso Zúñiga, Camila (Estado, Gobierno y Gestión Pública, 2020)
This article seeks to present the necessary elements to try to understand the situation of sexual political violence experienced in a focused and dis¬proportionate way by women and sexual dissidents between October and December 2019, giving an account of the continuous of this type of violence that has been exercised in our country since the dictatorship (and even further back), and in times of democracy, which has been expressed in the complaints received in the context of student demonstrations and recently, during the so-called “social explosion in Chile”. Furthermore, it seeks to contribute to public policies emanating from the State, which should pre¬vent, investigate, punish and eradicate such conduct by conceptualizing this type of violence through its use in armed conflicts and the case of Women victims of sexual torture v. Mexico, of the Inter-American Court of Human Rights.